Technological catch-up or neoclassical convergence? Identifying the channels of convergence for Italian regions - Scoppa, Vincenzo (Economics and Business Letters, 2013)
We investigate whether Italian regions haveconverged in terms of output per worker because of physical capitalaccumulation, human capital accumulation or thanks to technological catch-up. Inorder to identify channels of convergence we adopt the methodology recentlyproposed by Wong (2007) and Feyrer (2007) which combine growth accounting withconvergence regressions. Merging two datasets of regional economic accounts(ISTAT and CRENoS) to obtain longer time series, we show that convergence hasbeen realized mainly thanks to technological catch-up and, to some extent, throughhuman capital accumulation. On the other hand, physical capital has been afactor of divergence.